1991
DOI: 10.1002/cber.19911240516
|View full text |Cite
|
Sign up to set email alerts
|

Arsen(III)‐, Antimon(III)‐ und Bismuth(III)‐halogenid‐Komplexe des [2.2.2]Paracyclophans: Vom lockeren van‐der‐Waals‐Addukt zu stark gerichteten π‐Komplexen mit zwei‐ und dreifacher externer η6‐Koordination

Abstract: 2.2.2]Paracyclophane forms the adducts CZ4HZ4 . AsC13 (l), remains uncoordinated. Chlorine-bridging between antimony C24H24 . (SbC13)2 . C6H6 (2) and CZ4H2, . (BiCl& . C6H6 (3). atoms leads to tetrameric units (SbCI3), in the lattice. -In For solutions in polar solvents NMR spectra indicate extensive the bismuth compound 3 each benzene ring of the hydrocardissociation and/or fluxionality. In the crystals adduct 1 fea-bon is engaged in centroid ($)x complexation, with the BiC13 tures a weak addition of the AsC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 22 publications
6
34
0
Order By: Relevance
“…[16][17][18] To analyze this attractive interaction, DFT calculations were performed on the AsCl 3 -benzene dimer. [19] These studies revealed a lower limit for the binding energy of 7.4 kcal mol À1 for the arsenic-arene interaction, with CÀAs distances of 3.2-3.4 .…”
mentioning
confidence: 99%
“…[16][17][18] To analyze this attractive interaction, DFT calculations were performed on the AsCl 3 -benzene dimer. [19] These studies revealed a lower limit for the binding energy of 7.4 kcal mol À1 for the arsenic-arene interaction, with CÀAs distances of 3.2-3.4 .…”
mentioning
confidence: 99%
“…Previous work by Schmidbaur et al has shown that As III and other heavier main group elements with stereochemically active lone pairs can form close contacts with arene rings in the solid state 1618. To analyze this attractive interaction, DFT calculations were performed on the AsCl 3 –benzene dimer 19.…”
Section: Methodsmentioning
confidence: 99%
“…16 During the same period (mid to late 1980s), Schmidbaur and coworkers reported the groundbreaking complexes of pCp with some of the main-group metals. [17][18][19] Despite these contributions in synthesis of metallacyclophanes of pCp and Dp, a lot of effort is still required to explore the bonding properties of these complexes to make use of these promising p-donating ligands on industrial scale.…”
Section: Introductionmentioning
confidence: 99%